The voice of China : speeches of Generalissimo and Madame Chiang Kai-shek between December 7, 1941, and October 10, 1943 including some recent messages to British leaders and the British people - Kai-shek, Chiang (London : Hutchinson & Co., 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; China